Preparation of okara flour and its application in yogurt: Sensory evaluation (Research, Society and Development, 2021)
A way to increase nutritional value to yogurt is to add flours, but it is necessary to optimize formulations that meet consumer expectations. Therefore, this work’s objective was to elaborate and evaluate of okara flour and its application in strawberry skimmed yogurt. Okara flour stood out for its nutritional value, especially the high content of total dietary fiber (55.69%). In the first step of sensory analysis, the Ideal Test was applied with concentrations of 1%, 2%, 3%, 4% and 5% of okara flour. The ideal concentration was 0.87% of okara flour. In the second step, acceptance and purchase intention of yogurt with the addition of 0% (control), 0.87%, 1.67%, 2.67% and 5.40% of okara flour were evaluated. Yogurts without the addition of okara flour and 0.87% were the most accepted and had the most significant purchase intention. Therefore, it is concluded that it is possible to incorporate this flour in yogurt.